5
$\begingroup$

What is $$50^2\frac{{n\choose 50}}{{n\choose 49}}+49^2\frac{{n\choose 49}}{{n\choose 48}}...1^2\frac{{n\choose 1}}{{n\choose 0}}$$.

i.e. $$\sum_{k=1}^{50} \frac{k^2\binom n k}{\binom n {k-1}}= ?$$

$$\text{MY ATTEMPT}$$ When I plugged $n=50$ I got $22100$ as the series is wave like, with maximum at $25$ which is $25\times 26$. So I calculated it on a calculator and multiplied the summation till $25\times 26$ and got it. But I want to calculate the general formula for summation. The answer given is $425(3n-98)$. Thanks!

$\endgroup$
  • $\begingroup$ It's not clear where that first parenthesis is supposed to close, but do you want an alternating sum? $\endgroup$ – Thomas Andrews Feb 26 '16 at 13:55
  • $\begingroup$ If you'd fix your question so that people can figure out what you are asking, people might be able to help. Help people help you. $\endgroup$ – Thomas Andrews Feb 26 '16 at 14:03
5
$\begingroup$

$$\require{cancel} \sum_{r=1}^{50}r^2\frac{\binom nr}{\binom n{r-1}}\color{lightgrey}{=\sum_{r=1}^{50}r^\bcancel2\frac{\frac{\cancel{n(n-1)\cdots (n-r)}(n-r+1)}{\bcancel{r}\cancel{(r-1)!}}}{\frac{\cancel{n(n-1)\cdots (n-r)}}{\cancel{(r-1)!}}}}=\sum_{r=1}^{50}r(n-r+1)\\ =\sum_{r=1}^{50}nr-r(r-1)=\sum_{r=1}^{50} n\binom r1-2\binom {r}2\\ =n\binom {51}2-2\binom {51}3\\ =\frac 1{52}\binom {52}3(3n-98)\\ =425(3n-98)\quad\blacksquare$$


Note that if $n=50$, this reduces to $\binom {52}3$ as can be seen from above. This can also be proven directly as follows:

$$\sum_{r=1}^n r(n-r+1)=\sum_{r=1}^n\sum_{j=r}^nr=\sum_{j=1}^n\sum_{r=1}^j \binom r1=\sum_{j=1}^n\binom {j+1}2=\binom {n+2}3=\binom {52}3$$

$\endgroup$
5
$\begingroup$

If the sum that you're interested in is: $$ \sum_{k=1}^{50}\frac{k^2\binom{n}{k}}{\binom{n}{k-1}}, $$ Then, $$ \sum_{k=1}^{50}\frac{k^2\binom{n}{k}}{\binom{n}{k-1}}=\sum_{k=1}^{50}\frac{k^2(n-k+1)}{k}=\sum_{k=1}^{50}k(n-k+1)=(n+1)\sum_{k=1}^{50}k-\sum_{k=1}^{50}k^2. $$ Then, using the formulas $$ \sum_{k=1}^{50}k=\frac{50\cdot 51}{2}=1275 $$ and $$ \sum_{k=1}^{50}k^2=\frac{50\cdot 51\cdot 101}{6}=42925, $$ you will get the negative of the answer at the end of the post (perhaps due to the negative confusion in the discussion above).

$\endgroup$
  • 1
    $\begingroup$ which is $1275 n -41650 = 425(3n-98)$ and gives $22100$ when $n=50$. $\endgroup$ – Henry Feb 26 '16 at 14:18
5
$\begingroup$

What to compute is not very clear. Anyway, if you want the value of: $$ 50^2\frac{\binom{n}{50}}{\binom{n}{49}}+49^2\frac{\binom{n}{49}}{\binom{n}{48}}+\ldots+1^2\frac{\binom{n}{1}}{\binom{n}{0}}=50(n-49)+49(n-48)+\ldots+1(n-0)$$ you just need to recall that $\sum_{k=1}^{m}k = \frac{m(m+1)}{2}$ and $\sum_{k=1}^m k^2 = \frac{m(m+1)(2m+1)}{6}$.

$\endgroup$
3
$\begingroup$

Hint:

$$\frac{\binom{n}{p}}{\binom{n}{p-1}}=\frac{1}{p(n-p)}$$

$\endgroup$
  • $\begingroup$ Okay but how to deal with $1.50+49.2+48.3+....+26.25)$ $\endgroup$ – Archis Welankar Feb 26 '16 at 13:47
  • $\begingroup$ Can you check the location of the $n-p+1$ term from the $(n-(p-1))!$? $\endgroup$ – Michael Burr Feb 26 '16 at 14:11
  • $\begingroup$ $\frac{\binom{n}{p}}{\binom{n}{p-1}}=\frac{\frac{n!}{p!(n-p)!}}{\frac{n!}{(p-1)!(n-(p-1))!}}= \frac{(p-1)!(n-(p-1))!}{p!(n-p)!}= \frac{(p-1)!(n-p+1)!}{p!(n-p)!}= \frac{n-p+1}{p}$. $\endgroup$ – Michael Burr Feb 26 '16 at 14:21
  • $\begingroup$ perhaps you meant $\frac {\frac np}{\frac n{p-1}}=\frac 1{p(n-p)}$... $\endgroup$ – hypergeometric Feb 26 '16 at 14:38
  • 1
    $\begingroup$ I was referring to @Bacon's answer and trying to point that out. $\endgroup$ – hypergeometric Feb 26 '16 at 14:45
0
$\begingroup$

Each term has the form

$$ k^2\frac{\binom{n}{k}}{\binom{n}{k-1}} $$

We can simplify this

$$ k^2\frac{\binom{n}{k}}{\binom{n}{k-1}} = \frac{k^2\frac{n!}{(n-k)!k!}}{\frac{n!}{(n-k+1)!(k-1)!}} = \frac{k^2*n!(n-k+1)!(k-1)!}{n!*k!(n-k)!} = \frac{k^2(n-k+1)}{k} = k(n-k+1) $$

Thus

$$ \begin{align} \sum_{k=1}^{\hat{K}} k^2\frac{\binom{n}{k}}{\binom{n}{k-1}} &=& \sum_{k=1}^{\hat{K}} k(n-k+1) \\&=& (n+1)\sum_{k=1}^{\hat{K}} k - \sum_{k=1}^{\hat{K}} k^2 \\&=& \frac{\hat{K}(n+1)(\hat{K}+1)}{2} - \frac{\hat{K}(\hat{K}+1)(2\hat{K}+1)}{6} \\&=& \frac{\hat{K}(3n - 2\hat{K} + 2)(\hat{K}+1)}{6} \end{align} $$

Now, in your specific case, $\hat{K} = 50$, so we get a sum of $425(3n-98)$ by plugging this into the above.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.